2016
DOI: 10.1111/cod.12576
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin C on the elicitation of allergic contact dermatitis to p‐phenylenediamine

Abstract: The results suggest that treatment of the skin adjacent to the hair-bearing area with antioxidant could form part of a strategy to reduce the burden of cosmetic allergic contact dermatitis caused by hair dyeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…This is directly related to its co-factor activity for the synthesis of collagen, with impaired wound healing an early indicator of hypovitaminosis C [ 68 , 168 ]. Vitamin C turnover at wound sites, due to both local inflammation and the demands of increased collagen production, means that supplementation is useful, and both topical application and increased nutrient intake have been shown to be beneficial [ 166 , 169 , 170 ]. Supplementation with both vitamin C and vitamin E improved the rate of wound healing in children with extensive burns [ 171 ], and plasma vitamin C levels in smokers, abstaining smokers and non-smokers were positively associated with the rate of wound healing [ 162 ].…”
Section: Challenges To the Maintenance Of Skin Health And Potentiamentioning
confidence: 99%
“…This is directly related to its co-factor activity for the synthesis of collagen, with impaired wound healing an early indicator of hypovitaminosis C [ 68 , 168 ]. Vitamin C turnover at wound sites, due to both local inflammation and the demands of increased collagen production, means that supplementation is useful, and both topical application and increased nutrient intake have been shown to be beneficial [ 166 , 169 , 170 ]. Supplementation with both vitamin C and vitamin E improved the rate of wound healing in children with extensive burns [ 171 ], and plasma vitamin C levels in smokers, abstaining smokers and non-smokers were positively associated with the rate of wound healing [ 162 ].…”
Section: Challenges To the Maintenance Of Skin Health And Potentiamentioning
confidence: 99%
“…In view of the fact that many consumers, including those sensitised, prefer to nevertheless dye their hair (even if expecting symptoms of ACD after doing so [ 161 ]), alternative preventive strategies are being developed. One approach is to protect the surrounding glabrous skin by the application of a topical antioxidant (ascorbic acid) prior to hair dyeing, as has been quite successfully tried in 2 proof-of-principle studies [ 162 , 163 ]. The other approach is the development of presumably less-sensitising derivatives of e.g., p -phenylenediamine (PPD).…”
Section: Resultsmentioning
confidence: 99%
“…Vitamin C can also reduce allergies often encountered in dermatology. A case report concluded that it reduced the allergic contact dermatitis caused by hair dyes ( Basketter et al, 2016 ). The main component of hair dye is p -phenylenediamine.…”
Section: Vitamin C-related Skin Diseasesmentioning
confidence: 99%